Does i-scan improve adenoma detection rate compared to high-definition colonoscopy? A systematic review and meta-analysis - Aziz, Muhammad; Ahmed, Zohaib; Haghbin, Hossein; Pervez, Asad; Goyal, Hemant; Kamal, Faisal; Kobeissy, Abdallah; Nawras, Ali; Adler, Douglas G. (Endoscopy International Open, 2022)
Background and study aims Recent studies evaluated the impact of i-scan in improving the adenoma detection rate (ADR) compared to high-definition (HD) colonoscopy. We aimed to systematically review and analyze the impact of this technique.Methods A thorough search of the following databases was undertaken: PubMed/Medline, EMBASE, Cochrane and Web of Science. Full-text RCTs and cohort studies directly comparing i-scan and HD colonoscopy were deemed eligible for inclusion. Dichotomous outcomes were pooled and compared using random effects model and DerSimonian-Laird approach. For each outcome, relative risk (RR), 95 % confidence interval (CI), and P value was generated. P < 0.05 was considered statistically significant.Results A total of five studies with six arms were included in this analysis. A total of 2620 patients (mean age 58.6 ± 7.2 years and female proportion 44.8 %) completed the study and were included in our analysis. ADR was significantly higher with any i-scan (RR: 1.20, [CI: 1.06–1.34], P = 0.003) compared to HD colonoscopy. Subgroup analysis demonstrated that ADR was significantly higher using i-scan with surface and contrast enhancement only (RR: 1.25, [CI: 1.07–1.47], P = 0.004).Conclusions i-scan has the potential to increase ADR using the surface and contrast enhancement method. Future studies evaluating other outcomes of interest such as proximal adenomas and serrated lesions are warranted.